Psychological Characteristics of Athletes at the Student Education and Training Center - Dimyati (Faculty of Psychology, Universitas Surabaya, 2010)
The main objective of this study is to describe the psychological characteristics of the athletes of Archery, Tae Kwon Do, Pencak Silat (Indonesian Martial Art), Soccer, Athletics, Volleyball, and Sepak Takraw in the Center for Student Education and Training (CSET). The data were collected from 104 male and female athletes. The study shows that athletes of Soccer have the best scores in motivation, self-confidence, and mental preparation. Athletes of Tae Kwon Do have the best scores in control of anxiety and concentration, but the lowest scores in motivation. Athletes of Volleyball have the highest scores in team concern, but the lowest scores in concentration, self-confidence, and mental preparation, compared with the athletes from other sports, whereas the athletes of Athletics have the lowest scores in team concern, and the athletes of Pencak Silat have the lowest scores in control of anxiety compared to athletes from the other sports. Penelitian ini bertujuan untuk mendeskripsikan karakteristik psikologis atlet Panahan, Tae Kwon Do, Pencak Silat, Sepakbola, Atletik, Bola Voli, dan Sepak Takraw yang berada di Pusat Pendidikan dan Latihan Pelajar (PPLP). Data dikumpulkan dari 104 atlet pria dan wanita di Provinsi Jawa Tengah dan Daerah Istimewa Yogyakarta. Hasil penelitian menyimpulkan bahwa karakteristik psikologis atlet di PPLP adalah sebagai berikut: atlet Sepakbola memiliki motivasi, kepercayaan diri dan persiapan mental yang paling baik dibandingkan atlet cabang olahraga lainnya. Atlet Tae Kwon do memiliki kontrol kecemasan dan konsentrasi yang paling baik dibandingkan atlet cabang olahraga lainnya, namun memiliki motivasi yang paling rendah. Atlet Bola Voli memiliki perhatian tim yang paling tinggi dibandingkan atlet cabang olahraga lainnya, namun memiliki konsentrasi, kepercayaan diri dan persiapan mental yang paling rendah. Sedangkan atlet Atletik memiliki tingkat perhatian tim yang paling rendah, dan atlet Pencak Silat memiliki kontrol kecemasan yang paling rendah dibandingkan cabang olahraga lainnya.